Gestão dos resíduos sólidos urbanos domiciliares em São Paulo e Vancouver - Polzer, Verônica Rosária (2012)
Due to the large population growth of the cities, the proportional increase in the generation of waste and to the lack of public policies, the problem of the disposal of municipal solid waste (MSW) has become worse. In order to understand this situation, we developed two case studies in the city and the metropolitan area of São Paulo andVancouver, Canada. For both studies all forms of management of MSW were considered, from the collection, transfer station, composting, sorting of recycled materials, the incinerator with energy generation and, finally, the landfill, in order to identify the waste stream in the city, analyze the laws and master plans and existing waste management in order to check if the guidelines are being met and how cities are facing the problem. The integrated management of MSW is a public policy that aligned with the others, such as sanitation, health, housing and public transportation, ensures quality of life for citizens, being the urban planning responsible for integrate all these issues in the design of the city and the building so that the problem of MSW is minimized.